Improving Gender Literacy and Bullying Prevention through Strengthening Cultural Arts for Women's Empowerment and Child Protection in Denai Sarang Burung Village - Arlina Nurbaity Lubis; Eva Syahfitri Nasution; Hairani Siregar; Syarifah; Ramadani (International Publisher (YAPENBI), 2025)
Denai Sarang Burung Village has an important social issue to consider, namely child protection. One of the challenges faced by the community is cases of bullying that occur among children and adolescents. To anticipate and prevent this, an approach based on local wisdom and cultural arts is needed. The implementation of this community service activity successfully applied a participatory and collaborative approach, which encouraged the active involvement of the community, especially women, children, adolescents, and the village government as the main partners. In the implementation of community service activities, there was an increase in community knowledge, especially related to improving gender and bullying in an effort to strengthen a gender-based inclusive economy through women's empowerment and child protection. The formation of the Youth Monday Dance Studio under the name